1994
DOI: 10.1161/01.hyp.23.5.626
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of captopril and nitrendipine in transgenic rats with an extra renin gene.

Abstract: We investigated the acute effects of captopril and nitrendipine on renal function and sodium excretion in hypertensive, male, heterozygous transgenic rats harboring a mouse renin gene [TGR(mRen-2)27]. Both drugs reduced blood pressure dose dependently in conscious transgenic rats. The oral ED20 for captopril was 0.5 mg/kg and 2.7 mg/kg for nitrendipine. In orally salt-loaded (20 mL/kg saline) transgenic rats captopril (0.3 to 3.0 mg/kg) reduced sodium excretion by approximately 90% in the 6 hours after adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…We and oth ers have previously found similar glomerular filtration rates in TGR(mRen2)27 and Hannover Sprague-Dawley rats [7,12]. The ability of EL to lower blood pressure and alter pressure-diuresis-natriuresis responses of both CON and TGR rats could relate to differences in experimental conditions that favored fluid retention and enhanced angiotensin II (Ang II) production during the present study.…”
Section: Discussionsupporting
confidence: 68%
“…We and oth ers have previously found similar glomerular filtration rates in TGR(mRen2)27 and Hannover Sprague-Dawley rats [7,12]. The ability of EL to lower blood pressure and alter pressure-diuresis-natriuresis responses of both CON and TGR rats could relate to differences in experimental conditions that favored fluid retention and enhanced angiotensin II (Ang II) production during the present study.…”
Section: Discussionsupporting
confidence: 68%
“…These observations are in good agreement with previous studies in the contralateral kidney of 2-kidney, 1 clip Goldblatt hypertensive rats 26 and in the kidney of TGR rats, in which antidiuresis and antinatriuresis occurred, or GFR fell, after captopril or losartan treatment. 4,27 Because GFR and sodium and water excretion fell in parallel with a marked fall in MAP, these effects were most likely pressure-dependent in TGR rats. 5,9 Similarly, the observed higher basal renal hemodynamic and excretory function in TGR rats than in SD rats (Table) was also probably the result of severe hypertension and increased renal perfusion pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Although hypertension that occurs in this model is clearly a result of insertion of the mouse Ren-2 renin gene into the genome of the Hannover Sprague-Dawley (HanSD) rat, the exact pathophysiological mechanism responsible for the development of hypertension remains unknown [1]. Previous studies have implicated that the hypertension in TGR is angiotensin II (ANG II) dependent and that activation of the ANG II receptor subtype 1 is mainly responsible for the development of hypertension in this model [2][3][4][5]. However, it has been recently found that plasma and kidney ANG II concentrations are not elevated during the prehypertensive phase and during the developmental phase of hypertension in TGR [6].…”
Section: Introductionmentioning
confidence: 99%